Oceanographic, marine geological and sedimentary research in the coastal area of West Antarctica - O. Olshtynska; S. Kadurin; Ye. Nasedkin (Український антарктичний журнал, 2023)
We present the results of studying, mapping, and bathymetric profiling of the sea bottom relief from the research vessel Noosfera and the map of the Argentine Islands’ underwater relief based on current data. The paper contains a brief description of the material, granulometric (grain size analyses), and mineral composition of bottom sediments collected during the expedition in deep and shallow sites, as well as an analysis of sedimentation conditions in the region. We also provide the results of a study of the taxonomical and ecological diversity of siliceous microfossils of bottom sediments in Penola Strait; the material is illustrated with a table of images of diatoms studied using the scanning electron microscope. The fieldwork methods on the research vessel and in the laboratory and analytic works are described.